Every child, every day, back to play: the PICUstars protocol - implementation of a nurse-led PICU liberation program - M. Waak; J. Harnischfeger; A. Ferguson; K. Gibbons; K. H. Nguyen; D. Long (BMC, 2022)
Abstract Background As admissions to paediatric intensive care units (PICU) rise and mortality rates decline, the focus is shifting from survival to quality of survivorship. There is paucity of internationally accepted guidelines to manage complications like over-sedation, delirium, and immobility in the paediatric setting. These have a strong adverse impact on PICU recovery including healthcare costs and long-term functional disability. The A2F bundle (ABCDEF), or ICU Liberation, was developed to operationalise the multiple evidence-based guidelines addressing ICU-related complications and has been shown to improve clinical outcomes and health-care related costs in adult studies. However, there is little data on the effect of ICU Liberation bundle implementation in PICU. Methods PICU-STARS will be a single centre before-and-after after trial and implementation study. It is designed to evaluate if the multidimensional, nurse-led ICU Liberation model of care can be applied to the PICU and if it is successful in minimising PICU-related problems in a mixed quaternary PICU. In a prospective baseline measurement, the present practises of care in the PICU will be assessed in order to inform the adaptation and implementation of the PICU Liberation bundle. To assess feasibility, implementation outcomes, and intervention effectiveness, the implementation team will use the Consolidated Framework for Implementation Research (CIFR) and process assessment (mixed methods). The implementation process will be evaluated over time, with focus groups, interviews, questionnaires, and observations used to provide formative feedback. Over time, the barriers and enablers for successful implementation will be analysed, with recommendations based on "lessons learned." All outcomes will be reported using standard descriptive statistics and analytical techniques, with appropriate allowance for patient differentials in severity and relevant characteristics. Discussion The results will inform the fine-tune of the Liberation bundle adaptation and implementation process. The expected primary output is a detailed adaptation and implementation guideline, including clinical resources (and investment) required, to adopt PICU-STARS in other children's hospitals. Patient and public involvement statement The authors thank the PICU education and Liberation Implementation team, and our patients and families for their inspiration and valuable comments on protocol drafts. Results will be made available to critical care survivors, their caregivers, relevant societies, and other researchers. Trial registration ACTRN, ACTRN382863 . Registered 19/10/2021 - Retrospectively registered. Study status recruiting.